Candida albicans Factor H Binding Molecule Hgt1p – A Low Glucose-Induced Transmembrane Protein Is Trafficked to the Cell Wall and Impairs Phagocytosis and Killing by Human Neutrophils - Kenno, Samyr; Speth, Cornelia; Rambach, Günter; Binder, Ulrike; Chatterjee, Sneha; Caramalho, Rita; Haas, Hubertus; Lass-Flörl, Cornelia; Shaughnessy, Jutamas; Ram, Sanjay; Gow, Neil A. R.; Orth-Höller, Dorothea; et al. (Frontiers in Microbiology, 2019)
ABSTRACT Complement is a tightly controlled arm of the innate immune system, facilitating phagocytosis and killing of invading pathogens. Factor H (FH) is the main fluid-phase inhibitor of the alternative pathway. Many pathogens can hijack FH from the host and protect themselves from complement-dependent killing. Candida albicans is a clinically important opportunistic yeast, expressing different FH binding molecules on its cell surface, which allow complement evasion. One such FH binding molecule is the transmembrane protein “High affinity glucose transporter 1” (Hgt1p), involved in glucose metabolism. This study demonstrated that Hgt1p transcription and expression is induced and highest at the low, but physiological glucose concentration of 0.1%, why this concentration was used throughout the study. We also demonstrated the transport of Hgt1p to the fungal cell wall surface by vesicle trafficking and its release by exosomes containing Hgt1p integrated in the vesicular membrane. We corroborated Hgt1p as FH binding molecule. A polyclonal anti-Hgt1p antibody was created which interfered with the binding of FH, present in normal human serum to the fungal cell wall . A chimeric molecule consisting of FH domains 6 and 7 fused to human IgG1 Fc (FH6.7/Fc) even more comprehensively blocked FH binding, likely because FH6.7/Fc diverted FH away from fungal FH ligands other than Hgt1p. Reduced FH binding to the yeast was associated with a concomitant increase in C3b/iC3b deposition, resulted in significantly increased in vitro phagocytosis and killing by human neutrophils.In conclusion, Hgt1p also exhibits non-canonical functions such as binding FH after its export to the cell wall. Blocking Hgt1p-FH interactions may represent a tool to enhance complement activation on the fungal surface to promote phagocytosis and killing of C. albicans.